Analisis Yuridis Terhadap Narapidana Residivis Yang Mendapatkan Asimilasi Di Masa Pandemi Covid-19 ( Study Kasus Putusan Nomor : 1311/Pid.B/2020/PN Mks ) - Aswandi Syarif; Abdul Rahman; Nasrullah Arsyad (Qawanin Jurnal Ilmu Hukum, 2020)
This study aims to determine the basis for the provision of assimilation policies during the Covid-19 pandemic and to find out the reasons for the prosecutor to demand maximum punishment against recidivist defendants who received assimilation during the Covid-19 pandemic. This research uses normative research methods, covering primary and secondary legal materials. and tertiary, this research was conducted at the Makassar District Prosecutor Office at the Makassar Port, with the legal materials obtained and analyzed using a statutory approach to obtain a systematic picture. The results of this study indicate the provision of assimilation and integration for prisoners and children through the Regulation of the Minister of Law and Human Rights Number 10 of 2020 and the Decree of the Minister of Law and Human Rights Number 19 / PK / 01/04/2020, the basis for the provision of maximum demands by the prosecutor to recidivist convicts, namely the Attorney General circular. Research recommendations If this policy is seen as a strategy to reduce the spread of Covid-19 in prisons, the government should not immediately abandon the rules that have been made for the safety of the surrounding community. Abstrak Penelitian ini bertujuan untuk mengetahui dasar pemberian kebijakan asimilasi di masa pandemi covid-19 dan untuk mengetahui alasan JPU menuntut pidana maksimal kepada terdakwa residivis yang mandapatkan asimilasi di masa pandemi Covid-19.Penelitian ini menggunakan metode penelitian normatif, dengan cakupan bahan hukum primer, sekunder dan tersier, peneleitian ini dilakukan di Cabang Kejaksaan Negeri Makassar di Pelabuhan Makassar, dengan bahan hukum yang diperoleh akan dianalisis menggunakan pendekatan perundang-undangan untuk memperoleh gambaran yang sistematis. Hasil penelitian ini menunjukkan Pemberian asimilasi dan integrasi bagi narapidana dan anak melalui Peraturan Menteri Hukum dan Hak Asasi Manusia Nomor 10 Tahun 2020 dan Keputusan Menteri Hukum dan Hak Asasi Manusia Nomor 19/PK/01/04/2020, dasar pemberian tuntutan maksimal oleh JPU kepada narapidana residivis yaitu edaran Jaksa Agung. Rekomendasi penelitian Jika kebijakan ini dilihat sebagai salah satu strategi untuk mengurangi angka penyebaran Covid-19 di Lembaga pemasyarakatan, maka pemerintah tidak boleh serta merta meninggalkan aturan yang telah dibuat demi keamanan masyarakat sekitar.